Tuning the Aluminum Distribution in Zeolites to Increase their Performance in Acid-Catalyzed Reactions - Dědeček, Jiri; Tabor, Edyta; Sklenak, Stepan (ChemSusChem, 2019)
The organization of Al atoms in the framework of Si-rich zeolites is very important and includes two classes: (i) the Al siting that determines which individual, crystallographically distinguishable framework T sites are occupied by Al atoms and (ii) the Al distribution, which describes the relation of two or more Al atoms in the framework, their distances, and the possibility of neighboring Al atoms to cooperate in the formation of active sites. The organization of Al significantly affects the catalytic properties of Si-rich, zeolite-based catalysts in acid and redox catalysis. Herein, what is known about the organization of Al in the framework of industrially very important pentasil-ring Si-rich zeolites (ZSM-5, beta zeolite, mordenite, ferrierite, MCM-22, and TNU-9), as well as the very promising SSZ-13 Si-rich zeolite with the CHA structure, is summarized.
Keywords: NMR spectroscopy; catalytic activity; zeolites; FTIR spectroscopy; aluminum